anonymous
  • anonymous
Which solution is the solution to the following equation?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@jim_thompson5910
TheCatMan
  • TheCatMan
what are the choices
anonymous
  • anonymous
This is the correct equation: 2x + 4 =-8

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
x=-2 x=-1 x=-6 x=-8
TheCatMan
  • TheCatMan
try subtracting 4 from both sides to get 2x=-4 to simplify now try the rest
jim_thompson5910
  • jim_thompson5910
you wouldn't get 2x = -4
anonymous
  • anonymous
I think it x=-2
TheCatMan
  • TheCatMan
oops 2x=-12 sorry
jim_thompson5910
  • jim_thompson5910
2x = -12 is correct
anonymous
  • anonymous
Am I wrong?
jim_thompson5910
  • jim_thompson5910
x = -2 is incorrect
TheCatMan
  • TheCatMan
what is -12 divided by 2
anonymous
  • anonymous
-6
TheCatMan
  • TheCatMan
there you go
anonymous
  • anonymous
So its x= -6?
TheCatMan
  • TheCatMan
id say so
anonymous
  • anonymous
Jim do you agree?
jim_thompson5910
  • jim_thompson5910
I agree. The final answer is x = -6 we can check that claim by plugging it back into the original equation 2x + 4 =-8 2*(-6) + 4 =-8 ... replace every x with -6 -12+4 = -8 -8 = -8 Since -8 = -8 is a true equation, this means the original equation is true when x = -6. So that confirms the answer.
anonymous
  • anonymous
Great! Thanks guys!
jim_thompson5910
  • jim_thompson5910
no problem
TheCatMan
  • TheCatMan
any time

Looking for something else?

Not the answer you are looking for? Search for more explanations.